Acceptability and usability of smartphone-based brainwave entrainment technology used by individuals with chronic pain in a home setting. Issue 3 (August 2020) - Locke, Helen N; Brooks, Joanna; Arendsen, Laura J; Jacob, Nikhil Kurian; Casson, Alex; Jones, Anthony KP; Sivan, Manoj
Background: Brainwave entrainment (BWE) using rhythmic visual or auditory stimulation has many potential clinical applications, including the management of chronic pain, where there is a pressing need for novel, safe and effective treatments. The aim of this study was to gain qualitative feedback on the acceptability and usability of a novel BWE smartphone application, to ensure it meets the needs and wishes of end users. Methods: Fifteen participants with chronic pain used the application at home for 4 weeks. Semi-structured telephone interviews were then carried out. A template analysis approach was used to interpret the findings, with an initial coding template structured around the constructs of a theoretical framework for assessing acceptability of healthcare interventions. Structured data analysis generated a final modified coding structure, capturing themes generated across participants' accounts. Results: The four main themes were 'approach to trying out the app: affective attitude and ethicality', 'perceived effectiveness', 'opportunity costs and burden' and 'intervention coherence and self-efficacy'. All participants were willing to engage with the technology and welcomed it as an alternative approach to medications. Participants appreciated the simplicity of design and the ability to choose between visual or auditory stimulation. All the participants felt confident in using the application. Conclusion: The findings demonstrate preliminary support for the acceptability and usability of the BWE application. This is the first qualitative study of BWE to systematically assess these issues.